2023
DOI: 10.1002/aelm.202300056
|View full text |Cite
|
Sign up to set email alerts
|

Optical Verification of Physically Unclonable Function Devices Based on Spin‐Orbit Torque Switching

Abstract: Physically unclonable functions (PUFs) are used for various applications such as anticounterfeiting, authentication, and secret key generation. They are generally evaluated through electrical measurements, requiring much time and effort due to the many electrical connections required. This study proposes an optical verification of spin‐orbit torque (SOT) devices for PUF design. SOT devices have gained much attention because they resist degradation and thermal changes and can generate secret keys with high repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…(c) Flame and pressurized water stability tests of ultradurable embedded PUFs. (d) Comparison of the thermal stability of PUFs with the literature. ,,,, …”
Section: Resultsmentioning
confidence: 99%
“…(c) Flame and pressurized water stability tests of ultradurable embedded PUFs. (d) Comparison of the thermal stability of PUFs with the literature. ,,,, …”
Section: Resultsmentioning
confidence: 99%
“…The thermal stability of a PUF is crucial for the application in anticounterfeiting labels, ensuring reliability during shipping and storage. Figure (b) illustrates the comparison of thermal stability results for various PUFs. ,,,, The analysis focused on the peak temperature values to facilitate an accurate comparison. The results indicate that recent developments in PUF thermal stability have significantly extended the operational temperature range, increasing the stability threshold from 50 to 1000 °C.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Spintronic PUFs are being developed as an alternative to tackle these challenges and enable the development of on-chip PUFs integrated with CMOS technology. A recent study demonstrated the secure access and data protection capabilities of CMOS-integrated on-chip spintronic PUFs within in-memory computing . However, despite advances in spintronic or MRAM-based PUFs, some of the crucial PUF properties remain to be verified for practical applications.…”
mentioning
confidence: 99%